2014
DOI: 10.18632/oncotarget.2662
|View full text |Cite
|
Sign up to set email alerts
|

Reduced miR-126 expression facilitates angiogenesis of gastric cancer through its regulation on VEGF-A

Abstract: miR-126 is an endothelial-specific microRNA essential for governing vascular integrity and angiogenesis. Its role in tumor angiogenesis of gastric cancer (GC) is unclear. This study aimed at determining the role of miR-126 in GC angiogenesis. Down-regulation of miR-126 was found to inversely correlate with an increased microvessel density (MVD) and vascular endothelial growth factor A (VEGF-A) expression in gastric cancer tissues. Bioinformatics analysis and luciferase reporter assay revealed that miR-126 dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 56 publications
1
100
0
Order By: Relevance
“…For example, miRNA (miR)-126, originally identified as an endothelial-specific miRNA playing an essential role in angiogenesis and vascular integrity, [9][10][11] has been shown to function as a critical tumor suppressor in various types of solid tumors. 5,[12][13][14][15][16][17][18][19] In contrast, we have shown that miR-126 is aberrantly overexpressed and likely plays an oncogenic role in core binding factor (CBF) leukemia. 20 CBF leukemia is characterized by the presence of a t(8;21)(q22;q22) or an inv(16)(p13.1q22) chromosomal rearrangement, which accounts for ;20% to 30% of primary acute myeloid leukemia (AML) cases.…”
Section: Key Pointsmentioning
confidence: 99%
“…For example, miRNA (miR)-126, originally identified as an endothelial-specific miRNA playing an essential role in angiogenesis and vascular integrity, [9][10][11] has been shown to function as a critical tumor suppressor in various types of solid tumors. 5,[12][13][14][15][16][17][18][19] In contrast, we have shown that miR-126 is aberrantly overexpressed and likely plays an oncogenic role in core binding factor (CBF) leukemia. 20 CBF leukemia is characterized by the presence of a t(8;21)(q22;q22) or an inv(16)(p13.1q22) chromosomal rearrangement, which accounts for ;20% to 30% of primary acute myeloid leukemia (AML) cases.…”
Section: Key Pointsmentioning
confidence: 99%
“…In contrast, the down‐regulation of miR‐126 enhances VEGFA activity in lung cancer, oral cancer and breast cancer,53, 54, 55, 56 and the restoration of miR‐126 decreases VEGF and tumour size in lung cancer 53, 57. In addition, miR‐126 inhibits gastric cancer angiogenesis by significantly reducing VEGFA expression and the activation of its downstream genes, Akt/protein kinase B, mTOR and Erk1/2 in the gastric cancer cell lines SGC‐7901, MKN‐28 and MKN‐45 27, 58. Furthermore, miR‐126‐3p inhibits angiogenesis in HCC by reducing LRP6 and PIK3R2,59 Thus, this suggests that miR‐126 inhibits tumour angiogenesis.…”
Section: Mirnas That Target Genes Involved In Angiogenesismentioning
confidence: 99%
“…For example, in a study conducted by Fang et al,23 miR‐93 represses integrin‐β8 expression, thereby allowing spreading of endothelial cells, and consequently promotes angiogenesis in glioma. It is also revealed that miR‐126 facilitates angiogenesis of GC through regulating vascular endothelial growth factor (VEGF) level, which is an important regulator in vasculogenesis 18. These studies indicate that miRNAs are involved in angiogenesis, and aberrant expressions of these miRNAs are associated with etiology and progression in cancers 24, 25, 26, 27, 28.…”
Section: Discussionmentioning
confidence: 97%
“…Tumor‐related angiogenesis has been proved to be a pre‐condition for growth and progression of solid tumors, and anti‐angiogenesis such as small molecule tyrosine kinase inhibitor and monoclonal antibodies are widely studied in cancer therapies since the past decades 18, 19. Furthermore, increasing studies have demonstrated that several miRNAs take part in the processes of angiogenesis and they play crucial roles in the progress or prognosis of cancers such as hepatocellular carcinoma, human colon cancer, and bladder cancer 20, 21, 22.…”
Section: Discussionmentioning
confidence: 99%